A large Cirroteuthis magna (Cephalopoda: Cirroctopoda) caught on the Cape Verde Terrace (North Atlantic) - Collins, Martin A.; O'Dea, Mary; Henriques, Camila (Journal of the Marine Biological Association of the United Kingdom, 2001)
A large, mature, female cirrate octopod, Cirroteuthis magna , was caught in a research trawl at 3200-m depth on the Cape Verde Terrace off the west African coast in November 1999. It is only the fourth recorded specimen of this species and the largest specimen (1,700 mm TL; 330 mm ML) of cirrate octopod ever caught. Detailed measurements were taken of the fresh and preserved specimen and indicated considerable shrinkage (17–32%) during formalin preservation. Careful dissection revealed large mature eggs (12·5–14 mm long) in the proximal oviduct, and a wide range of egg sizes and development stages in the ovary. The taxonomy and ecology of the species is briefly discussed.